Mutual Funding - Gil-Bazo, Javier; Hoffmann, Peter; Mayordomo, Sergio (Review of Financial Studies, 2020)
Abstract Using data on Spanish mutual funds, we show that bank-affiliated funds provide funding support to their parent company via purchases of bonds in the primary market. Support from affiliated funds is more sizeable in crisis times and for riskier banks. These trades generate negative abnormal returns and thus benefit banks at the expense of fund investors. To minimize negative effects on their asset management business, banks concentrate the burden of funding support in funds without performance fees and those catering to retail investors. We provide evidence consistent with funding support helping to limit credit rationing over the 2008–2012 period.